Workshop and Assistance with Article Publication as an Effort for Teachers’ Continuous Professional Development - Mochamad Abdul Basir; Imam Kusmaryono; Dyana Wijayanti; Nila Ubaidah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Teachers play an important role in realizing national education goals. Teachers need to be aware and determined to develop themselves to become professionals. Continuous self-development can provide added value for teachers, professional organizations, and the quality of education. One of the self-development that teachers can do is scientific publications. However, some teachers at SMA Negeri 6 Semarang have difficulty writing scientific papers. Apart from that, teachers are also confused about publishing their articles. Therefore, the Sultan Agung Islamic University lecturer service team is trying to solve this problem through workshops and assistance in writing articles. The workshop participants were 56 teachers. The problem-solving method in this service activity is through a group-based, comprehensive, and resource-potential approach. Implementation of service activities consists of four stages including socialization, workshops, mentoring, and evaluation. As a result of the workshop activities, it was found that 71% of participants were able to publish articles in the form of best practice reports, newspaper articles, and journal articles.